A SURVEY OF PROTEIN CLASSIFICATION USING NEURAL NETWORK. - NURAIDA, WASLEE (Universiti malaysia sarawak (UNIMAS), 2004)
The application of neural network has been applied extensively these days, this include the biological application of protein classification and DNA analysis. Neural network classification method has been developed as an alternative approach to the large database search or organizational problem. This study covers the previous research that had been done by researchers on neural network proteins classification problem. It covers the processes of protein sequences classification, various neural network architecture used, proteins encoding and decoding techniques. This study also include on how proteins can be classified by using neural network classification method, and also some traditional techniques. The importance of neural network is also discussed.